2012
DOI: 10.1105/tpc.112.097394
|View full text |Cite
|
Sign up to set email alerts
|

DWARF AND LOW-TILLERING Acts as a Direct Downstream Target of a GSK3/SHAGGY-Like Kinase to Mediate Brassinosteroid Responses in Rice

Abstract: In Arabidopsis thaliana, the GSK3/SHAGGY-like kinase BRASSINOSTEROID-INSENSITIVE2 (BIN2) plays a critical role in the brassinosteroid (BR) signaling pathway by negatively regulating the activities of bri1-EMS-SUPPRESSOR1/BRASSINAZOLE-RESISTANT1 family transcription factors that regulate the expression of downstream BR-responsive genes. In this study, we analyzed the function of a rice (Oryza sativa) GSK3/SHAGGY-like kinase (GSK2), which is one of the orthologs of BIN2. Overexpression of GSK2 (Go) led to plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
295
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(321 citation statements)
references
References 86 publications
7
295
0
1
Order By: Relevance
“…Firstly, over-expression of OsMIR396d in rice resulted in increased leaf angle and semidwarf phenotype ( Figs. 1 and 2), which was similar to the phenotype of rice plants with accumulated BR or with enhanced BR signal (Tanaka et al, 2009;Tong et al, , 2012Zhang et al, 2009Zhang et al, , 2012. Secondly, we demonstrated that the CGTGT/CG element in the OsMIR396d promoter was directly bound by OsBZR1 using yeast one-hybrid experiment and EMSA assay in vitro and also ChIP-qPCR detection in vivo.…”
Section: Osbzr1 Targets Osmir396d To Control Leaf Angle Through Osgrfmentioning
confidence: 56%
See 1 more Smart Citation
“…Firstly, over-expression of OsMIR396d in rice resulted in increased leaf angle and semidwarf phenotype ( Figs. 1 and 2), which was similar to the phenotype of rice plants with accumulated BR or with enhanced BR signal (Tanaka et al, 2009;Tong et al, , 2012Zhang et al, 2009Zhang et al, , 2012. Secondly, we demonstrated that the CGTGT/CG element in the OsMIR396d promoter was directly bound by OsBZR1 using yeast one-hybrid experiment and EMSA assay in vitro and also ChIP-qPCR detection in vivo.…”
Section: Osbzr1 Targets Osmir396d To Control Leaf Angle Through Osgrfmentioning
confidence: 56%
“…Then, the signal is passed along to a key negative regulator, BRASSINOSTEROID-INSENSITIVE 2 (BIN2), which is dephosphorylated by BRI1 SUPPRESSOR 1 (Li et al, 2001;Mora-Garciá et al, 2004;Kim et al, 2011). In rice, the dephosphorylation of GSK3/SHAGGY-like Kinase (OsGSK2, a rice homolog of Arabidopsis BIN2) releases its suppression on BRASSINAZOLE-RESISTANT1 (OsBZR1), LEAF AND TILLER ANGLE INCREASED CONTROLLER (OsLIC), DWARF AND LOW-TILLERING (OsDLT), OVATE Family Protein 8, and REDUCED LEAF ANGLE1 to activate BR response and increase leaf angle (Bai et al, 2007;Wang, L et al, 2008;Tong et al, , 2012Zhang et al, 2012;Yang et al, 2016, Qiao et al, 2017. The kinase activity of OsGSK2 can also be directly inhibited by membrane protein GW5 (quantitative trait locus for grain width and weight on chromosome 5), which is a calmodulin-binding protein (Liu et al, 2017).…”
mentioning
confidence: 99%
“…Genes GRAS19 (Chen et al, 2013), LAZY1 (Li et al, 2007), CYP51G3 (Xia et al, 2015), and GSR1 ) present high expression levels at the lamina joint, validating their roles in lamina joint development. In addition, genes involved in the biosynthesis and signaling of BR and auxin, which have been implicated in important roles in the leaf angle, present diverse expression patterns, including decreased expression (CYP51G3 and CYCU4:1), increased expression (DLT [Tong et al, 2009] and GRAS19 and GH3-2 [Tong et al, 2012]), constant high expression levels (LIC and LAZY1 [Zhang et al, 2012]), and constant low expression levels (ILI1 [Zhang et al, 2009a] and REL1 [Chen et al, 2015a]), suggesting the complex regulation of leaf angles via different pathways.…”
Section: Cytological Observation Reveals the Distinct Characteristicsmentioning
confidence: 99%
“…12,13 The mechanisms by which BES1/BZR1 represses thousands of genes have just begun to be revealed. [15][16][17][18][19] While BIN2 phosphorylates and inhibits the functions of most of its known substrates, recent studies on HAT1 and MYBL2 demonstrated that BIN2 phosphorylation can have different outcomes.…”
mentioning
confidence: 99%